Attenuation of sleep deprivation dependent deterioration in male fertility parameters by vitamin C - Nermin I. Rizk; Mohamed S. Rizk; Asmaa S. Mohamed; Yahya M. Naguib (BMC, 2020)
Abstract Purpose Male fertility is multifaceted and its integrity is as well multifactorial. Normal spermatogenesis is dependent on competent testicular function; namely normal anatomy, histology, physiology and hormonal regulation. Lifestyle stressors, including sleep interruption and even deprivation, have been shown to seriously impact male fertility. We studied here both the effects and the possible underlying mechanisms of vitamin C on male fertility in sleep deprived rats. Methods Thirty male Wistar albino rats were used in the present study. Rats were divided (10/group) into: control (remained in their cages with free access to food and water), sleep deprivation (SD) group (subjected to paradoxical sleep deprivation for 5 consequent days, rats received intra-peritoneal injections of vehicle daily throughout the sleep deprivation), and sleep deprivation vitamin C-treated (SDC) group (subjected to sleep deprivation for 5 consequent days with concomitant intra-peritoneal injections of 100 mg/kg/day vitamin C). Sperm analysis, hormonal assay, and measurement of serum oxidative stress and inflammatory markers were performed. Testicular gene expression of Nrf2 and NF-κβ was assessed. Structural changes were evaluated by testicular histopathology, while PCNA immunostaining was conducted to assess spermatogenesis. Results Sleep deprivation had significantly altered sperm motility, viability, morphology and count. Serum levels of cortisol, corticosterone, IL-6, IL-17, MDA were increased, while testosterone and TAC levels were decreased. Testicular gene expression of Nrf2 was decreased, while NF-κβ was increased. Sleep deprivation caused structural changes in the testes, and PCNA immunostaining showed defective spermatogenesis. Administration of vitamin C significantly countered sleep deprivation induced deterioration in male fertility parameters. Conclusion Treatment with vitamin C enhanced booth testicular structure and function in sleep deprived rats. Vitamin C could be a potential fertility enhancer against lifestyle stressors.